'CHEMICAL ASSEMBLY' SYNTHESIS OF PIEZO-PHASE NANOSIZE POWDERS USED FOR PIEZO-CERAMICS MANUFACTURING - Larisa E. PUSTOVAYA; Aleksey A. NESTEROV; Vladimir V. КRIKOV; Alexander S. PAKHOMOV (Advanced Engineering Research, 2010)
'Chemical assembly' method of the nanoprecursors multifunctional matrixes which skeleton structure is similar to the structure of a final reaction product is developed. The method is used for the synthesis of various oxide phases on the basis of zirconate-titanate and lead niobate. The method allows to control the structure, size of particles, deficiency of the produced powders, and electrophysical parameters of piezo-ceramics made on their basis. Application prospects of high values of d31 и d33 и Кр as ultrasonic detectors, acoustic-surface waves filters, etc., are shown.